Effectuation Principles as an Entrepreneurial Strategy during a Crisis in the Hotel Industry in Indonesia - Gunawan , Inge; Hashim , Norashidah (Journal of Ecohumanism, 2024)
The principle of effectuation is a fascinating concept in entrepreneurship that emphasizes a flexible and adaptive approach to business creation. This approach is particularly beneficial in unpredictable contexts, encouraging entrepreneurs to leverage their current resources and networks. The aim of this study is to identify the entrepreneurial strategies employed by boutique hotels, grounded in five principles of effectuation, to navigate a crisis. This study utilizes semi-structured interviews as the primary method for collecting data on crisis management among business owners or senior executives. The respondents in this study comprised ten decision-makers from seven boutique hotels, including owners and top-level management. The findings indicate that boutique hotel entrepreneurs employed effectuation principles as an entrepreneurial strategy during a crisis, enabling the hotels to navigate the challenges effectively. This study's findings will enhance existing research in the hotel sector and elucidate entrepreneurial reactions to crises.